Promotion of Student Engagement Through the Application of Good Practices in Nursing Online Education. Issue 2 (17th April 2023) - Hampton, Debra; Hardin-Fanning, Fran; Culp-Roche, Amanda; Hensley, Angie; Wilson, Jessica L.
Abstract : The purpose of this article is to review Chickering and Gamson's principles of good practice in teaching and to illustrate their applicability to nursing online education delivery. An additional purpose is to present examples of teaching methods used by faculty to promote engagement in online education courses during the pandemic. The original 7 best practices in education, including ( a ) encourages contact between students and faculty, ( b ) develops reciprocity and cooperation among students, ( c ) uses active learning techniques, ( d ) gives prompt feedback, ( e ) emphasizes time on task, ( f ) communicates high expectations, and ( g ) respects diverse talents and ways of learning, remain evidence-based guidelines today. The authors recommend the addition of 2 new best practices: ( a ) incorporating assignment flexibility to meet student learning preferences; and ( b ) applying learning to real-life situations. Having evidence-based guidelines for supporting the role of a teacher in the online learning setting is of paramount importance.